A THEORETICAL FOUNDATIONS OF CONTRADICTORY LANGUAGE UNITS: THEORETICAL FOUNDATIONS OF CONTRADICTORY LANGUAGE UNITS - Nuradinova, Gulmira (Журнал иностранных языков и лингвистики, 2022)
Contrast is one of the most important methods of the language of fiction and journalism that allowing to reveal the complex dialectical the contradiction of the depicted